CAGE21-6 Cruise Report: Hydrocarbon leakage in Hopendjupet, central Barents Sea - Winsborrow, Monica; Knies, Jochen (CAGE – Centre for Arctic Gas Hydrate, Environment and Climate Report Series, 2022)
CAGE21-6 will visit the Hjopendjupet Seepage area between 5-16th December and use an ROV to study the seafloor for the first time. The cruise may be known as: CAGE21_6